Analysis of Values in Surah An-Nur Verse 31 and Al-Ahzab Verse 59: A Qualitative Research Approach - Jamil, Salbiah (MANDAILING GLOBAL EDUKASIA, 2024)
In the Qur'an, Surah An-Nur verse 31 and Al-Ahzab verse 59, Allah has explained how to dress properly, including: Clothing must cover the entire body, except for certain parts, clothing must not be transparent or show the curves of the body, clothing must not be scented or perfumed, clothing must not be decorative, clothing must not resemble men's clothing or non-Muslim clothing, clothing must be free from all kinds of pictures or paintings. Clothing must not contain wasteful elements, must not be syuhran clothing (grand/famous clothing), must be made of clean and halal goods, clothing must be free from anything that causes arrogance or arrogance. But there are still many teenagers who do not dress in an Islamic way. The purpose of the discussion is to find out the educational values ​​contained therein. The results of this study indicate that the educational values ​​in Surah An-Nur verse 31 and Al-Ahzab verse 59 can be classified into three, namely: Education of Faith, Morals, and Worship. In Aqidah education which is related to the private parts, guarding one's gaze, and everything that Allah commands in the Qur'an and Hadith must be believed with the heart, spoken with the tongue and practiced with deeds. Likewise, the values ​​of worship in relation to the private parts, so that all the commands of Allah SWT that we carry out can function as a form of our devotion to Allah. Meanwhile, moral values ​​are all our actions or behavior or deeds in carrying out Allah's commands, by maintaining a view of maintaining genitals and so on, meaning that we have morals as commanded by Allah, which are contained in Surah An-Nur verse 31 and Al-Ahzab verse 59 so that they can be internalized and practiced in everyday life. To get perfect results, first carry out a review or library research. The discussion of this thesis is a descriptive method by studying the Al-Qur'anul Karim, tafsir books, books, writings or other sources related to this discussion by reading, recording and collecting information that is related to the problem being discussed. By studying the educational values ​​in the letter An-Nur verse 31 and Al-Ahzab verse 59 means that we will be closer to Allah SWT and practice more all the contents contained in the Al-Qur'anul Karim as a guideline for us Muslims, so that it can be applied in everyday life.